Enhanced cardiac S100A1 expression improves recovery from Gglobal Ischemia-reperfusion injury - Jungi, Silvan; Fu, X.; Segiser, A.; Busch, Martin; Most, Patrick; Fiedler, M.; Carrel, T.; Tevaearai Stahel, H.; Longnus, S. L.; Most, Henriette (Journal of cardiovascular translational research, 2018)
Gene-targeted therapy with the inotropic Ca2 + -sensor protein S100A1 rescues contractile function in post-ischemic heart failure and is being developed towards clinical trials. Its proven beneficial effect on cardiac metabolism and mitochondrial function suggests a cardioprotective effect of S100A1 in myocardial ischemia-reperfusion injury (IRI). Fivefold cardiomyocyte-specific S100A1 overexpressing, isolated rat hearts perfused in working mode were subjected to 28 min ischemia (37 °C) followed by 60 min reperfusion. S100A1 overexpressing hearts showed superior hemodynamic recover: Left ventricular pressure recovered to 57 ± 7.3% of baseline compared to 51 ± 4.6% in control (p = 0.025), this effect mirrored in LV work and dP/dt(max). Troponin T and lactate dehydrogenase was decreased in the S100A1 group, as well as FoxO pro-apoptotic transcription factor, indicating less tissue necrosis, whereas phosphocreatine content was higher after reperfusion. This is the first report of a cardioprotective effect of S100A1 overexpression in a global IRI model.